Albernoa revisited: tracking social capital in a Portuguese village - Carmo, R. M. (Sociologia Ruralis, 2010)
In the field of rural studies, social capital has been seen as an important factor that can contribute decisively to the development of rural communities. The aim of this article is to identify some of the social problems that are affecting the capacity of one particular village to generate and improve new forms of social capital. Albernoa is a Portuguese village situated in the region of Alentejo (southern Portugal). Over the last three decades some profound and contradictory changes have occurred in the rural environment: progressive population ageing, continuous depopulation and, simultaneously, the recent trend towards suburbanisation. Internally, the population of Albernoa has profound difficulty in reinforcing the community ties capable of organizing and improving on some collective projects, like the local sports club. The residents are deeply divided in terms of collective trust. Some local leaders complain about this problem, which affects the levels of social capital among the villagers.